Critical Issues in Psychological Services Within Italian Schools: Definition, Contexts, Interventions, and Legislation for Vulnerable Populations - Simona Grilli; Giulio Perrotta; Stefano Eleuteri; Irene Petruccelli (Children)
Background: This paper presents a comprehensive literature review that investigates the pivotal role of school psychologists within the Italian educational context, highlighting their importance in promoting mental health and students’ well-being, emphasizing the importance of a comprehensive school psychology evidence-based service to facilitate the personal and professional development of both students and staff. Methods: To conduct this review, we utilized databases such as Scopus, ResearchGate, PsycINFO, and PubMed to access recent scientific literature related to school psychologists in Italy, focusing primarily on studies published between 2018 and 2025. We employed keywords including “school psychologist in Italy”, “mental health”, “COVID-19”, “COVID-19 and school psychologists”, and “school psychologist legislation in Italy” to guide our search. Results: By synthesizing the existing literature, this study aims to explore the integration and effectiveness of psychological services in Italian schools, particularly in light of the challenges posed by the COVID-19 pandemic. This review provides an overview of the current state of school psychology evidence-based services in Italy, with particular attention to the emotional and psychological challenges exacerbated by the pandemic. This event that has profoundly impacted community life highlighted the importance of mental health, prompting Italy to enhance the presence of psychologists within schools. Furthermore, this review critically analyzes the existing laws and psychological frameworks, drawing on data from an extensive examination of legislative documents and the previous literature regarding the implementation of school psychology services. The findings reveal that 69.2% of Italian schools adopted a school psychology service following legislative initiatives, aimed at addressing the trauma and discomfort caused by the pandemic. Conclusions: Despite this progress, the presence of this figure is still rare and while significant steps have been taken, a shift towards a more preventative and holistic model is currently essential.